Drugs in cancer care - Midgley, Rachel S.; Middleton, Mark R.; Dickman, Andrew; Kerr, David J. ([Oxford] : Oxford University Press, 2013)
Providing an overview of pharmacology and prescribing advice'Drugs in Cancer Care' contains over 90 drug monographs presented in easy-to-use and accessbile A-Z format. This detailed yet concise handbook is ideal for all healthcare professionals involved in the provision of cancer care.
Includes index.
Description based on online resource; title from home page (viewed on October 7, 2013).
Keywords: Cancer -- Chemotherapy